Shifts in pore connectivity from precipitation versus groundwater rewetting increases soil carbon loss after drought. Issue 1 (December 2017) - Smith, A. Peyton; Bond-Lamberty, Ben; Benscoter, Brian; Tfaily, Malak; Hinkle, C. Ross; Liu, Chongxuan; Bailey, Vanessa
Abstract Droughts and other extreme precipitation events are predicted to increase in intensity, duration, and extent, with uncertain implications for terrestrial carbon (C) sequestration. Soil wetting from above (precipitation) results in a characteristically different pattern of pore-filling than wetting from below (groundwater), with larger, well-connected pores filling before finer pore spaces, unlike groundwater rise in which capillary forces saturate the finest pores first. Here we demonstrate that pore-scale wetting patterns interact with antecedent soil moisture conditions to alter pore-scale, core-scale, and field-scale C dynamics. Drought legacy and wetting direction are perhaps more important determinants of short-term C mineralization than current soil moisture content in these soils. Our results highlight that microbial access to C is not solely limited by physical protection, but also by drought or wetting-induced shifts in hydrologic connectivity. We argue that models should treat soil moisture within a three-dimensional framework emphasizing hydrologic conduits for C and resource diffusion. The impacts of top down (precipitation) and bottom-up (groundwater rise) wetting processes on carbon sequestration are poorly understood. Here, the authors use incubation experiments to show that drought legacy and pore-scale wetting patterns are important factors controlling short-term carbon dynamics.